Testicular Expression of NGF, TrkA and p75 During Seasonal Spermatogenesis of the Wild Ground Squirrel (Citellus Dauricus Brandt) - Zhang, H. (Eur J Histochem, 2015)
The nerve growth factor (NGF) not only has an essential effect on the nervous system, but also plays an important role in a variety of non-neuronal systems, such as the reproductive system. The aim of this study was to compare the quality and quantity in expression of NGF and its receptors (TrkA and p75) in testes of the wild ground squirrel during the breeding and nonbreeding seasons. Immunolocalization for NGF was detected mainly in Leydig cells and Sertoli cells in testes of the breeding and nonbreeding seasons. The immunoreactivity of TrkA was highest in the elongated spermatids, whereas p75 in spermatogonia and spermatocytes in testes of the breeding season. In the nonbreeding season testes, TrkA showed positive immunostainings in Leydig cells, spermatogonia and primary spermatocytes, while p75 showed positive signals in spermatogonia and primary spermatocytes. Consistent with the immunohistochemical results, the mean mRNA and protein level of NGF and TrkA were higher in the testes of the breeding season than in non-breeding season, and then decreased to a relatively low level in the nonbreeding season. In addition, the concentration of plasma gonadotropins and testosterone were assayed by radioimmunoassay (RIA), and the results showed a significant difference between the breeding and nonbreeding seasons with higher concentrations in breeding season. In conclusion, these results of this study provide the first evidence on the potential involvement of NGF and its receptor, TrkA and p75 in the seasonal spermatogenesis and testicular function change of the wild ground squirrel.